2019
DOI: 10.3390/catal9080661
|View full text |Cite
|
Sign up to set email alerts
|

Waste Seashells as a Highly Active Catalyst for Cyclopentanone Self-Aldol Condensation

Abstract: For the first time, waste-seashell-derived CaO catalysts were used as high-performance solid base catalysts for cyclopentanone self-condensation, which is an important reaction in bio-jet fuel or perfume precursor synthesis. Among the investigated seashell-derived catalysts, Scapharca Broughtonii-derived CaO catalyst (S-shell-750) exhibited the highest dimer yield (92.1%), which was comparable with commercial CaO (88.2%). The activity sequence of different catalysts was consistent with the CaO purity sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Moreover, Al 2 O 3 (5.10 %), Na 2 O (0.33 %), CaO (0.30 %) were found as minor impurity components over KOH/diatomite. According to the literature, these minor components can also catalyze the reaction [25] . Thus, it can be concluded that there is synergistic effect between KOH and these impurity components of diatomite.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, Al 2 O 3 (5.10 %), Na 2 O (0.33 %), CaO (0.30 %) were found as minor impurity components over KOH/diatomite. According to the literature, these minor components can also catalyze the reaction [25] . Thus, it can be concluded that there is synergistic effect between KOH and these impurity components of diatomite.…”
Section: Resultsmentioning
confidence: 96%
“…It was discovered that the waste shells are beneficial for the production of a wide range of value-added chemicals and products, such as 1,2,3-triazoles [44], cyclopentanone [45], 7,8-dihydro-4H-chromen-5(6H)-one [46], dimethyl carbonate [47], steam gasification [48], wastewater treatment [49], soil improvement [50], Portland cement replacement [51] and artificial stone [52]. Xiong et al [44] studied the synthesis of 1,2,3-triazoles catalyzed by waste oyster shell powders (OSPs)-supported CuBr catalyst (OSPs-CuBr).…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that the prepared OSPs-CuBr catalysts showed high catalytic activity with cost-effectiveness for the larger-scale synthesis of 1,4-disubstituted 1,2,3-triazoles. Sheng et al [45] investigated the multiple characteristics of the Scapharca Broughtonii shell, conch shell and oyster shell derived catalyst for cyclopentanone self-aldol condensation. Dimer obtained from the self-aldol condensation pathway of cyclopentanone can be used as a high-density fuel or perfume precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclopentanone can be obtained (at high carbon yields of 62-95.8%) through the aqueous phase selectively hydrogenation and rearrangement of furfural [34][35][36][37][38]. High density fuels were prepared by self aldol condensation of cyclopentanone and hydrodeoxygenation [39][40][41][42]. In some studies, diesel and jet fuel range cycloalkanes were produced by the aldol condensation of furfural and cyclopentanone [43][44][45][46], followed by HDO.…”
Section: Introductionmentioning
confidence: 99%